KAJIAN ASPEK SOSIAL EKONOMI MASYARAKAT DALAM RANGKA PERLINDUNGAN DAN PELESTARIAN POPULASI DAN HABITAT JENIS ENDEMIK SULAWESI HOPEA CELEBICA DAN VATICA FLAVOVIRENS - Yumna Yumna (Universitas Andi Djemma Palopo, 2017)
The potential of natural resources and human resources (forest dwellers), occupy the same position in the importance of sustainable forest management. This study aims to determine the socio-economic conditions in order to protection and preservation of the population and habitat of endemic species Hopea celebica and Vatica flavovirens. This study examines some parameters of the social and economy (the level of community participation, the tendency of society to a certain type of behavior on the forest, people's behavior toward the tree species, the public perception of the type of endemic, people's incomes, land for a decent life, use of environmental services, history and culture area of each village). The results showed the Local Wisdom Society is closely linked to the protection and preservation program habitats and populations of endemic species. The level of participation of the two villages, including High. Society has a tendency towards certain commodities namely plant pepper. People's behavior toward forests affected by distance from the house very close to the forest so that almost every day in the woods, with the purpose of hunting, non-wood, wood (for the house, for sale, pole pepper), and gardening / open land. This type of wood is taken is the type that grow, with equipment such as axes, and are used for the manufacture of home. The level knowledge of public about the species endemic to Sulawesi (meranti, rode, and dama'dere) is very low. Welfare level is quite good, and the average land managed by the current wider than the minimum land area for a decent life, and land productivity is high, so the potential for farm expansion does not occur.